Spatial Sustainability, Trade and Indicators - Jeroen C.J.M. van den Bergh; Harmen Verbruggen (Tinbergen Institute, 1998)
The search for frameworks and indicators of sustainable development has taken a prominent place in this journal. However, some specific aspects have received little or no attention, notably the spatial dimension and the role of international trade in indicator development. Moreover, many sustainable development indicators comprise implicit valuations, weighting schemes and policy objectives, which are insufficiently recognised as such. This contribution tries to highlight these issues by means of a review of a recently proposed indicator for ecological–economic analysis, namely the ecological footprint, that has been developed by Wackernagel and Rees. Its concept and calculation procedure are criticised on a number of points, and it is concluded that the Ecological Footprint is not the comprehensive and transparent planning tool as is often assumed. In explaining our position we will argue that spatial sustainability and regional sustainable development have not been precisely discussed so far, neither in the literature on trade and environment, nor in that on sustainable development. We will defend the view that trade can contribute positively and negatively to environmental unsustainability. Consequently, indicators and models are needed that allow for analysing interactions and trade-offs between such opposite effects.
Keywords: 330; Carrying capacity; Indicators of sustainable development; Interregional trade; International economics; Regional sustainability; Trade theory; Land use; Sustainable trade; Nachhaltige Entwicklung; Wirtschaftsindikator; Theorie